Kepelbagaian warisan geologi persisiran pantai di Kepulauan Langkawi - Komoo, Ibrahim; Unjah, Tanot; Ismail, Syafrina (2004)
Langkawi is known internationally as one of the main tourist destination in Malaysia, blessed with earth heritage that has great potential to be develop in a sustainable manner. Knowledge of the diverse physical heritage (geology and landscape) found along the coast plays an important role to unravel its potential as a new product of tourism. Coastal landscape is characterised by rocky, pebbly, sandy and muddy (including mangrove) beaches together with small islands. The rocky beach unfolds a diverse range of rocks and earth features, in which retains the historical record of the origin of Malaysia Land that took place 550. It also reveals the coastal landscape formation which crafted by waves activities. A section of the coastal outcrop represent a unique historical site and scenic landscape. This paper illustrates the diverse geological heritage and landscape found in Datai and Burau Bay and introduces rocky beach as a prospect, in which a major component of the environment, for development of beach resources.